Petrography and composition of Martian regolith breccia meteorite Northwest Africa 7475. (February 2015) - Wittmann, Axel; Korotev, Randy L.; Jolliff, Bradley L.; Irving, Anthony J.; Moser, Desmond E.; Barker, Ivan; Rumble, Douglas
Abstract The Northwest Africa (NWA) 7475 meteorite is one of the several stones of paired regolith breccias from Mars based on petrography, oxygen isotope, mineral compositions, and bulk rock compositions. Its inventory of lithic clasts is dominated by vitrophyre impact melts that were emplaced while they were still molten. Other clast types include crystallized impact melt rocks, evolved plutonic rocks, possible basalts, contact metamorphosed rocks, and siltstones. Impact spherules and vitrophyre shards record airborne transport, and accreted dust rims were sintered on most clasts, presumably during residence in an ejecta plume. The clast assemblage records at least three impact events, one that formed an impact melt sheet on Mars ≤4.4 Ga ago, a second that assembled NWA 7475 from impactites associated with the impact melt sheet at 1.7–1.4 Ga, and a third that launched NWA 7475 from Mars ~5 Ma ago. Mildly shocked pyroxene and plagioclase constrain shock metamorphic conditions during launch to >5 and <15 GPa. The mild postshock‐heating that resulted from these shock pressures would have been insufficient to sterilize this water‐bearing lithology during launch. Magnetite, maghemite, and pyrite are likely products of secondary alteration on Mars. Textural relationships suggest that calcium‐carbonate and goethite are probably of terrestrial origin, yet trace element chemistry indicates relatively low terrestrial alteration. Comparison of Mars Odyssey gamma‐ray spectrometer data with the Fe and Th abundances of NWA 7475 points to a provenance in the ancient southern highlands of Mars. Gratteri crater, with an age of ~5 Ma and an apparent diameter of 6.9 km, marks one possible launch site of NWA 7475.